Le parler jeune dans la ville d’Oran : entre tendances langagières et créativité linguistique - Chernouhi, Ahmed (Journal of Ecohumanism, 2025)
This contribution highlights the speech of young people in the city of Oran and the linguistic procedures used in communicative situations, which constitute the effects of linguistic trends and linguistic creativity. It should be noted that the linguistic landscape of Oran is characterised by the existence and/or coexistence of various idioms forming a language repertoire specific to each young speaker. French, which is taught in Algeria from primary school onwards, is undoubtedly used in most of the language practices of young people, and this language is in constant contact with other languages in all language exchanges, which is decidedly multilingual. The aim of this study is therefore to examine the language practices of young people in Oran and to determine, among other things, the role of bilingualism and plurilingualism in the emergence of recurrent linguistic phenomena in the speech of young people in resolutely spontaneous communication situations, namely: diglossia, the linguistic continuum, borrowing, codic alternation, the mixing of languages and other linguistic forms.